Evaluation of liver parenchymal changes in patients with reduced left ventricular ejection fraction using cardiac MRI T1 mapping and extracellular volume fraction - Sercan Şahin; Hazal Öykü Yılmaz; Can Ilgın; Nilgün Işıksalan Özbülbül (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Background and objectives Congestive hepatopathy (CH) is a diffuse parenchymal liver disease resulting from chronic passive congestion due to cardiac pathology. This retrospective cross-sectional study aims to evaluate hepatic congestion in patients with left ventricular ejection fraction (LVEF)